AGE, BREASTFEEDING HISTORY, AND HORMONAL CONTRACEPTIVE USE AS PREDICTORS OF BREAST CANCER INCIDENCE AT NTB PROVINCIAL HOSPITAL - Mileniasari, Ni Made Srileona; Suanjaya, Made Agus; Pramana, Kadek Dwi; Mulianti, Rizki (UNG, 2026)
Breast cancer is a major health problem in women whose incidence continues to increase, including in Nusa Tenggara Barat (NTB) Province, so that scientific evidence-based prevention efforts are needed. The novelty of this study lies in the simultaneous analysis of age, breastfeeding history, and hormonal contraceptive use as independent risk factors for breast cancer in the local NTB population using a multivariate approach. This study aims to analyze the relationship between age, breastfeeding history, and hormonal contraceptive use with breast cancer incidence at the NTB Provincial Hospital. The research used an observational analytical design with a retrospective case-control approach, involving 110 respondents (55 cases and 55 controls) and medical record data from 2024, with univariate analysis, a bivariate Chi-Square test, and multivariate logistic regression. The results showed that age 40 years and hormonal contraceptive use were associated with an increased risk of breast cancer, while breastfeeding history was protective, and all three variables remained significant in the multivariate analysis, with hormonal contraceptive use as the most dominant factor. The conclusion of this study states that age, breastfeeding history, and hormonal contraceptive use are independent risk factors for breast cancer. Therefore, strengthening health education, early detection in at-risk groups, and appropriate contraceptive counseling are needed as a breast cancer prevention effort in NTB Province.